Qualitative Assessment on Effectiveness of Security Approaches towards Safeguarding NFC Devices & Services - Anusha R; Veena Devi Shastrimat V (Institute of Advanced Engineering and Science, 2018)
The increasing pace in the wireless communication taking momentum in the market of commercial application where a significant trade-off between user-experience and security demands exists. The Near Field Communication or NFC is one such communication trend which is effectively adopted by the user worldwide to make touchless operation using their mobile device. Although, it is claimed that NFC incorporates some of the standard encryption but existing researchers fails to prove that their electromagnetic signals are not so difficult to compromise to result in collateral damage to user's resources. Thus, there exist research work towards strengthing security system, but there is yet to report on any standard security protocol or framework to ensure the highest resiliency. This paper provides a comprehensive visualization towards the effectiveness of existing research approaches to formulate the research trend and gap.